Conservative Technique Using Oral Dressing Material for Wound Dehiscence after Ridge Augmentation: A Technical Report with a Case Series - Jeong-Kui Ku; Yeong Kon Jeong; Yong-Suk Choi; Taeyeong Kim; In-Woo Cho; Dae Ho Leem (Applied Sciences, 2021)
Wound dehiscence is the most frequent complication after ridge augmentation and causes postoperative infection, inadequate bone healing, or graft failure. In the oral cavity, conservative treatment for dehiscence is difficult to maintain until secondary healing occurs because of its normal flora, dynamic masticatory muscle movement, and humid environment. This paper reports an effective conservative method using an oral wound dressing material with an omnivec splint and presents three wound dehiscence cases: (1) autogenous tooth bone graft material with a collagen membrane, with dehiscence occurring at postoperative 5 days. (2) Autogenous bone graft covering titanium mesh, with dehiscence occurring at postoperative three weeks. The mesh was removed after 10 weeks with histologic analysis. (3) Autogenous bone and autogenous tooth bone graft covering a titanium mesh, with dehiscence occurring at postoperative 1 week. The exposed titanium mesh was maintained for 6 months after the graft. All cases achieved secondary healing and acceptable outcomes for a dental implant by conservative treatment without infection after the dehiscence after ridge augmentation.